Tobacco Consumption and Legislations Regarding Tobacco Use in India - Is It Time for A Policy Change? - Anantha Eashwar V M; Timsi Jain; Madhumita JR; Keerthana R (Medsci Publications, 2022)
One of the most consumed and readily available products causing psychological dependence among the population is tobacco and its related products. Though the government of India is undertaking measures to reduce tobacco consumption, factors like easy availability, lack of monitoring of tobacco use among youngsters, low cost and rapid absorption into the central nervous system is prompting people from a young age to the elderly to consume tobacco-related products. Legislative measures to reduce tobacco consumption seldom reach or benefit people as laws differ across States. This increases the prevalence of respiratory diseases like Chronic Obstructive Pulmonary Disease (COPD) and lung cancer. This review article discusses the status of tobacco consumption in India with emphasis on tobacco-related legislation in States and associated health inequities.